2006
DOI: 10.2115/fiber.62.63
|View full text |Cite
|
Sign up to set email alerts
|

One-pot Enzymatic Synthesis of Poly(L,L-lactide) by Immobilized Lipase Catalyst

Abstract: Abstract:The ring-opening polymerization of L,L-lactide by using immobilized lipase Candida Antarctica (Novozym 435) as a catalyst at a temperature of 100 o C in bulk was conducted. This process was found to yield the corresponding poly(L,L-lactide) (PLLA) with weight-average of molecular weights of about 2,440 and a polydispersity index of 2.63. It was observed that the increase of the reaction time and amount of enzyme catalyst resulted in the polylactides with higher molecular weights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Its 1H-NMR analyses showed that 15% of LLA was consumed after one day and it was completely depleted after 7 days. On the basis of our experimental results, which are similar to earlier reported works [7,8], it can be concluded that, ROP of LLA proceeds without biocatalyst both in IL media and in bulk. In addition, 1H-NMR, 13C NMR (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Its 1H-NMR analyses showed that 15% of LLA was consumed after one day and it was completely depleted after 7 days. On the basis of our experimental results, which are similar to earlier reported works [7,8], it can be concluded that, ROP of LLA proceeds without biocatalyst both in IL media and in bulk. In addition, 1H-NMR, 13C NMR (Fig.…”
Section: Resultssupporting
confidence: 92%
“…3) were obtained after 3 days of reaction without biocatalyst (Table 1). This same result has been reported in the synthesis in bulk using this biocatalyst [8] and other enzymatic preparations [7,11].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations